2012
DOI: 10.1016/j.jelechem.2012.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Is hydrogen gas in water present as bubbles or hydrated form?

Abstract: a b s t r a c tWhen hydrogen gas is bubbled into water, it may well be present as stabilized bubbles rather than hydrated hydrogen molecules, as in the spontaneous emulsification at oil|water interfaces without surfactant. On this prediction, we used dynamic light scattering (DLS) to find bubbles 0.4-0.5 lm in diameter, which were stable for more than 9 h. The intensity of the scattering light, which was proved to be proportional to concentrations of polystyrene latex suspensions, was also kept in solution in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…As already mentioned, this refinement of the model seems necessary for a full, accurate description, since most of the H 2 in the electrolyte is known to be present in the form of small gas bubbles, whereas only hydrated H 2 molecules in the liquid participate in the electrode reactions [14].…”
Section: Transport Of Ions and Molecules In The Electrolytementioning
confidence: 99%
See 3 more Smart Citations
“…As already mentioned, this refinement of the model seems necessary for a full, accurate description, since most of the H 2 in the electrolyte is known to be present in the form of small gas bubbles, whereas only hydrated H 2 molecules in the liquid participate in the electrode reactions [14].…”
Section: Transport Of Ions and Molecules In The Electrolytementioning
confidence: 99%
“…However, most of this is apparently in the form of submicron (diameter ≈ 440 nm) gas bubbles that also serve as the nucleation centers for bubble growth, when H 2 is produced, and less than 10% is in hydrated form that may react at the electrodes [14,15]. We assume that in equilibrium the effective density of the gas corresponds to a concentration of 0.77 mM and the concentration of hydrated H 2 molecules is one tenth of that, i.e., 0.077 mM.…”
Section: Mass Exchange Of H 2 Between Gas and Liquid Phasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, after gas/liquid separation, electrolytes coming from each compartment (O 2 and H 2 ) are usually mixed together and reinjected in the electrolyser. A recent work [58] showed that hydrogen bubbles in aqueous solutions, even at atmospheric pressure, are very stable: continuing to have a diameter of around 0.4 μm for an unexpectedly long time (after 9 h, only 50% of the number of bubbles had disappeared). 1) Consequences are that the purity of produced gases decreases rapidly when increasing the pressure.…”
Section: Advantages and Disadvantagesmentioning
confidence: 99%